Validity and Practicality of Reaction Rate Module Based on Problem Based Learning Integrated Socio-Scientific Issues for Phase F - Feyges Frilla Firanti; Andromeda; Alizar; Desy Kurniawati (Jurnal Penelitian Pendidikan IPA, 2025)
design stages, this research only focuses on the development stage, namely the validity and practicality tests. The research instruments used were validation questionnaires and practicality questionnaires for teachers and students. The validity test was carried out by 5 expert teams and the practicality test was carried out on two chemistry teachers and 34 phase F students. The results of construct and content validity tests were obtained at 0.89 and 0.93 with valid categories. The results of the module's practicality test conducted by teachers and students amounted to 92.92% and 87.45% with a very practical category. The results showed that a valid and practical PBL-based reaction rate module integrated with SSI was produced for phase F students.